A new possibility of self-consistent field theory: Obtaining native states of proteins. (3rd January 2018) - Duan, Hua; Li, Jianfeng; Zhang, Hongdong; Qiu, Feng
Abstract: In this work, the lattice self-consistent field theory (SCFT) is modified to obtain the native state with a definite conformation of a given protein chain. The method has been applied to the simplest protein model – the 2D HP protein model. Starting with a random initial external field, a specific conformation of the given protein corresponding to the native state marvelously emerges after a series of self-consistent iterations. The modified lattice SCFT has been also employed to obtain other degenerate native states of the HP protein through a single SCFT calculation while previous methods can obtain these states only by a series of simulations. Graphical abstract: A Definite Native State of an HP Protein is Obtained by a Lattice SCFT Calculation from a Random Initial Field. Image 1 Highlights: A lattice SCFT is modified to obtain the native state of proteins. The native state with a definite configuration emerges in SCFT calculations. Spontaneous symmetry breaking phenomenon is observed for the two-monomer fixing case.